Surgical treatment of acquired tracheoesophageal fistula caused by balloon dilatation of corrosive esophageal stricture in a child - Stojakov, Dejan; Miličković, Maja; Minić, Predrag; Vukadin, Miroslav; Stanković, Nikola; Savić, Djordje (Vojnosanitetski pregled, 2021)
Introduction. Tracheoesophageal fistula (TEF) as a complication of balloon dilatation (BD) of corrosive esophageal stricture is a very rare and serious condition. Life threatening aspiration pneumonia requests urgent lungs’ protection, but overall treatment strategy is not clearly defined. Case report. Twenty-month-old female child accidentally ingested a household bleach. Caustic injury of esophagus was healing with development of strictures of cervical and proximal thoracic esophagus. TEF was developed during the third BD. Healing of TEF and pulmonary infection was achieved by exclusion of the esophagus (pharyngostoma and feeding gastrostomy together) with prolonged tracheobronchial intubation and toilette. Retrosternal colon interposition was performed a year later, with excellent functional results over four-year follow-up. Conclusion. Esophageal exclusion in the first stage, and pharyngoesophageal reconstruction in the second stage, is a useful therapeutic option in the treatment of TEF caused by balloon dilatation of corrosive esophageal stricture in children.